Sub-structure and mechanical properties of twist channel angular pressed aluminium - Kocich, Radim; Kunčická, Lenka; Král, Petr; Macháčková, Adéla (Materials characterization, 2016)
The twist channel angular pressing (TCAP) method was developed with the aim to increase the effectiveness of severe plastic deformation (SPD) technologies. This study was focused on investigations of grains sizes, textures and sub-structure within a TCAP-processed commercial aluminium sample. Measurements of microhardness and tensile strengths were performed to evaluate mechanical properties of the processed material. To point out the effectiveness of TCAP, the results were compared to Al samples processed by equal channel angular pressing (ECAP) via A and Bc routes. Almost 70% of the grains within the sample processed by a single TCAP pass were smaller than 5μm comparing to approximately 40% and 50% within samples processed by two ECAP passes via A and Bc routes, respectively. The texture of the TCAP sample exhibited a combination of A ideal and B fibre preferential texture components and its sub-structure exhibited a higher degree of development than the sub-structures in all the ECAP-processed samples. The TCAP sample also exhibited the highest increases in the mechanical properties. The microhardness was more than twice as high as for the original state, while the yield strength achieved almost 230MPa. [Display omitted] •Structure development after twist channel angular pressing (TCAP) was investigated.•Efficiency of TCAP was higher than two passes equal channel angular pressing (ECAP).•Mechanical properties increased more after one TCAP pass than after two ECAP passes.•Grain size refined down to 6μm after one TCAP pass.